Radio Pensiunan: Ruang Sosial dan Hiburan bagi Pensiunan di Era Media Baru - Subekti, Komarudin; Vahista, Salwa Lila; Ramdhani, Muhamad (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2026)
Retirement is often associated with decreased activity and reduced social interaction. However, humans are fundamentally social creatures who need interpersonal and interactional communication. Through online broadcasts and community activities, Radio Pensiunan provides a communication medium that maintains interconnectedness between individuals while providing a space for retirees to express themselves, allowing them to remain active, productive, and feel meaningful.This research examines Radio Pensiunan as a community media outlet based on new media and information and communication technology (ICT), serving as a social space, entertainment, and a platform for nostalgia for retirees. Amidst the dominance of digital platforms that primarily target the younger generation, Radio Pensiunan offers a specific segmentation through the playback of old-school music, a classic broadcasting style, and community interactions that strengthen a sense of togetherness.The theoretical framework used is mass communication theory and new media theory to examine the transformation of community radio in the digital ecosystem, as well as interpersonal and interactional communication theory to explain how emotional closeness is formed between broadcasters and listeners. This research is expected to contribute to the study of the adaptation of traditional media in the digital era, while also emphasizing the role of community media as a relevant means of nostalgia and entertainment for retirees.